Internet-based Cognitive Behavioral Therapy for DSM-IV Sexual Dysfunctions in Breast Cancer Survivors: Predictors of Treatment Response. Issue 3 (3rd July 2018) - Hummel, Susanna B.; van Lankveld, Jacques J. D. M.; Oldenburg, Hester S. A.; Hahn, Daniela E. E.; Broomans, Eva; Aaronson, Neil K.
Abstract: Objectives : We evaluated factors predictive of the effect of internet-based cognitive behavioral therapy (CBT) in breast cancer survivors with a sexual dysfunction. Methods : Fifty-five women completed questionnaires assessing sexual functioning and distress at baseline and post-CBT. Results : Higher therapy compliance and better partner baseline sexual functioning predicted better post-CBT sexual functioning. Higher therapy compliance and higher partner relationship satisfaction predicted lower sexual distress. Therapy compliance, in turn, was predicted by active partner involvement in therapy and a stronger therapeutic relationship. Conclusions : To increase the effect of internet-based CBT, we recommend partner involvement in therapy and establishing a strong therapeutic relationship.